Characteristic of pedagogic techniques of persistence nurture in sportsmen with defects of mental functioning in process of emotional-will training - Babich, N.L. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: to characterize pedagogic techniques of persistence nurture of sportsmen with defects of mental functioning in process of emotional-will training and test their effectiveness. Material: 11 swimmers (functional class S-14) with defects of mental development (light form of mental deficiency) were involved in the research. Ability for persistence was diagnosed in test 4×50 meters by free style. Results: in sportsmen with defects of mental functioning persistence is restricted by degree of supreme psychic functions’ affections and depend on combination of psychological-pedagogic factors of influence. We characterized specific features of adapted pedagogic techniques for persistence nurture in such sportsmen. It was found that one of conditions of high sport results’ achievement was maximal manifestation of willpower by sportsman. Conclusions: persons with mental deficiency are characterized by inability for regulation of own behavior. It proves that it is necessary to apply correctly directed methods, means and pedagogic techniques in process of emotional-will training of the sportsmen. Effectiveness of the offered pedagogic techniques was proved by test 4×50 meters (free style) (р<0.05).